Outcome of Obstetric Patients Admitted to a Medical Intensive Care Unit in Southeastern Turkey - Uysal, Nevin; Dikensoy, Ebru; Balat, Özcan (Gynecology Obstetrics & Reproductive Medicine, 2009)
OBJECTIVE:Obstetric patients represent <2 % of intensive care unit (ICU) admissions with a corresponding ICU utilization rate of 0.17-0.4% of deliveries. There is no data about the rate of ICU utilization by obstetrical patients or the outcome of these patients admitted to ICU in Turkey. The purpose of this study was to look at the outcomes of obstetric patients admitted to a medical ICU at a major referral center in southeastern Turkey. MATERIAL AND METHOD:Prospectively entered ICU database and patient charts were reviewed for obstetric admissions between February 2007 and May 2008. RESULTS:Forty-two obstetric patients were admitted to the ICU representing 4.4% of ICU admissions and 5.1 % of deliveries. Seventy-six percent was admitted in the postpartum period. Main reasons for ICU admission were hemodynamic instability (43%) and mental status change (36%). Fifty-five percent of the admission were due to obstetrical reasons. Hypertensive states of pregnancy (38%) and postpartum bleeding (14%) were the most common obstetrical reasons. CONCLUSION:Maternal mortality was 4.8% in our all patients.Two observed mortalities were due to neurological complications: hemorrhagic CVA in the setting of eclampsia and uncal herniation secondary to cavernous sinus thrombosis.